Two-Word Usage: Cognitive Development And The Beginnings Of Combinatorial Utterance. - Zakaria, Noraizzah Haji (Universiti Sains Malaysia, 1990)
For centuries parents, scholars and teachers have been fascinated and amazed fay the phenomenon of language acquisition in children. How are we to account for the fact that "virtually every child, without undergoing special training, exposed to surface structure of language in many interactional contexts, builds for himself in a short period of time and at an early stage in his cognitive a deep leve1, abstract, and highly complex system of linguistic structure and use . " (In Lindfors; 1987) Hence a number of theories have been formulated on the acquisition of language.